Preparation of Bioplastics from Pineapple Peel Nata and Rice Washing Water - Sani; Amanah Nur Febrianti; Dwika Mahtris Nandani Putri; Dwi Hery Astuti (Future Science, 2023)
Bioplastics are plastics made from natural materials such as starch, seeds, and tubers, then added cellulose such as nata. Bioplastics are easily degraded by microorganisms or moisture. Pineapple peel is a part of pineapple fruit that has been underutilized so it ends up as waste. The high carbohydrate content in pineapple fruit skin can potentially be used as raw material for making nata, with the addition of rice washing water which contains carbohydrates, starch, vitamin B1, vitamin B6, and vitamin B3 which can be utilized by microorganisms as a medium for making nata. The resulting nata is used as raw material for making bioplastics because the cellulose content in nata is quite high. The results of the analysis of cellulose content in the nata produced amounted to 42.78%. This study aims to make bioplastics from pineapple peel nata and rice washing water that meet the Japanesse Industrial Standard (JIS). The method of making bioplastics used is the solution casting method. The variables used in making this bioplastic are 15 grams of nata, plus 3.5 grams of chitosan with 500 rpm stirring for 10 minutes at 70 °C with the addition of glycerol variations of 2; 2.5; 3; 3.5, and 4% and variations of CMC ingredients 4; 6; 8; 10 and 12%. From the results of the study, the best results of bioplastics, namely the tensile strength value of 0.51 MPa, elongation of 71.49%, water resistance of 55.61%, and biodegradation of 35.81%, were obtained in the addition of CMC 8% and glycerol added 3.5%. The results of the bioplastic SEM test obtained a very tight and fairly flat bioplastic structure. In addition, the FTIR test found that bioplastics have 5 peaks where the 5 peaks represent the forming functional groups of bioplastics such as O-H functional groups.